An activated carbon composite material and its preparation method and application

By loading nano -zero -priced iron and nano -silver on the activated carbon, it solves the problem of insufficient adsorption efficiency and lack of selectivity when removing low concentration pollutants in water removal. Risk of ion loss.

CN116870869BActive Publication Date: 2025-01-28INST OF URBAN ENVIRONMENT CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311074203.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-01-28
Estimated Expiration
2043-08-24

Smart Images

  • Figure CN116870869B_ABST
    Figure CN116870869B_ABST
Patent Text Reader

Abstract

The present invention provides an activated carbon composite material and a preparation method and application thereof. The activated carbon composite material comprises activated carbon and an active component loaded on the activated carbon; the active component comprises zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the activated carbon composite material of the present invention can enhance the hydrophobicity, electron transfer ability and pollutant molecule selectivity of the composite material surface, and at the same time has antibacterial properties, can weaken the release of silver ions, integrates the advantages of efficient electron transfer, strong surface hydrophobicity, high pollutant selectivity and inhibition of microbial reproduction on the carbon surface, can safely and effectively adsorb and degrade or convert low-concentration pollutants in drinking water, and can significantly improve the water purification ability of activated carbon from many aspects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmentally friendly material preparation, and relates to an activated carbon composite material and a preparation method and application thereof. Background Art

[0002] The safety and cleanliness of terminal drinking water are receiving more and more attention. It is particularly important to develop technologies and materials that can effectively remove low-concentration pollutants from terminal drinking water. Activated carbon has the characteristics of rich pore structure and surface chemical properties, low ash content, broad spectrum, etc., and has been widely used in terminal water purification. However, with the continuous detection of new pollutants in water, activated carbon faces problems such as insufficient adsorption efficiency leading to large usage, mismatch between pore structure and surface hydrophilicity, and pollutants only undergoing phase transfer without being degraded. Therefore, on the basis of activated carbon, the above problems can be solved through modification to enhance the application potential of activated carbon under the new situation.

[0003] Specifically, pollutants in water are widely distributed and have their own physical and chemical properties. Based on the analysis of the physical and chemical properties of pollutants in water and the judgment of the molecular interaction and electron transfer mechanism between them and the activated carbon surface, the development of corresponding activated carbon-based composite materials has become one of the effective ways to solve the above problems. Loading nanomaterials on the surface of activated carbon is one of the effective ways to improve adsorption performance.

[0004] Due to the nano-size effect, the number of atoms on the surface of nanomaterials increases exponentially, thereby increasing the number of active sites on the surface and improving the reaction efficiency. For example, activated carbon-loaded nano zero-valent iron composites can synergize the high surface reactivity of nano zero-valent iron and the adsorption performance of activated carbon to improve the removal efficiency of pollutants in water, while degradation or transformation may occur; activated carbon-loaded graphene composites can synergize the high electron transfer efficiency, high specific surface area and hydrophobicity of graphene, reduce the cost of graphene use, and effectively improve the adsorption efficiency and capacity of hydrophobic macromolecular organic matter in water; activated carbon-loaded nanosilver can inhibit the growth of surface microorganisms.

[0005] The above-mentioned existing technologies have correspondingly improved the ability of activated carbon to remove pollutants, but at the same time have the following two defects: (1) Nano-zero-valent iron and nano-silver are more likely to react with water molecules, resulting in low selectivity for target pollutants and a low effective reaction ratio; (2) Application risks brought by nanomaterials. Nano-zero-valent iron and nano-silver are easily lost after reacting with water, which may cause secondary pollution problems.

[0006] Based on the above research, there is a need to provide an activated carbon composite material, which can reduce the probability of reaction between the material surface and water molecules, improve the electron transfer efficiency of nano zero-valent iron, and solve the problem of surface microbial film growth. Summary of the invention

[0007] The purpose of the present invention is to provide an activated carbon composite material and a preparation method and application thereof, wherein the activated carbon composite material is simultaneously loaded with sulfided nano-zero-valent iron and sulfided nano-silver, thereby improving the selectivity of pollutants, reducing the risk of metal ion loss, inhibiting the growth of microbial film on the surface of activated carbon, and in situ degrading some organic matter in water.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides an activated carbon composite material, the activated carbon composite material comprising activated carbon and an active component supported on the activated carbon;

[0010] The active components include zero-valent iron and silver. The surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide.

[0011] The surface of the activated carbon of the present invention is loaded with sulfidized zero-valent iron and silver, which solves the problem that zero-valent iron and silver are easy to react with water molecules, resulting in weak selectivity for target pollutants, low effective reaction ratio, and easy loss of zero-valent iron and silver after reaction with water, resulting in secondary pollution. In addition, the material can enhance the hydrophobicity, electron transfer ability and pollutant molecule selectivity of the composite material surface, and at the same time has antibacterial properties and weakens the release of silver ions. It combines the advantages of efficient electron transfer, strong surface hydrophobicity, high pollutant selectivity and inhibition of microbial reproduction on the carbon surface, and can safely and effectively adsorb and degrade or convert low-concentration pollutants in drinking water, such as trihalomethanes, N-nitrosodimethylamine (NDMA), lead or cadmium, etc., and significantly improves the water purification ability of activated carbon from many aspects.

[0012] Preferably, the particle size range of the zero-valent iron is 20-50 nm, which means that the minimum particle size of the zero-valent iron is above 20 nm, for example, it can be 20 nm, 22 nm, 24 nm or 26 nm, and the maximum particle size of the zero-valent iron is below 50 nm, for example, it can be 50 nm, 48 nm, 46 nm or 44 nm. The thickness range of the iron sulfide on the surface of the zero-valent iron is 1-3 nm, which means that the minimum thickness of the iron sulfide is above 1 nm, for example, it can be 1 nm, 1.2 nm or 1.4 nm, and the maximum thickness of the iron sulfide is below 3 nm, for example, it can be 3 nm, 2.8 nm or 2.6 nm, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] Preferably, the silver particle size range is 10-30nm, which means that the minimum silver particle size is above 10nm, such as 10nm, 12nm or 14nm, and the maximum is below 30nm, such as 30nm, 28nm or 26nm. The thickness of the silver sulfide on the silver surface ranges from 1-3nm, which means that the minimum thickness of the silver sulfide is above 1nm, such as 1nm, 1.2nm or 1.4nm, and the maximum thickness of the iron sulfide is below 3nm, such as 3nm, 2.8nm or 2.6nm, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0014] In a second aspect, the present invention provides a method for preparing the activated carbon composite material as described in the first aspect, wherein the preparation method comprises a liquid phase reduction method or a carbon thermal reduction method;

[0015] The liquid phase reduction method comprises the following steps:

[0016] (1) mixing the activated carbon with the impregnation solution to obtain a mixed solution;

[0017] The impregnation solution includes Fe 2+ and Ag + ;

[0018] (2) adding a reducing agent to the mixed solution of step (1) for reduction, and then adding a vulcanizing agent for vulcanization to obtain the activated carbon composite material;

[0019] The carbothermal reduction method comprises the following steps:

[0020] (i) impregnating activated carbon and / or biomass carbonized material, and then performing solid-liquid separation to obtain an impregnated material;

[0021] The impregnation solution used in the impregnation includes Fe 2+ and Ag + ;

[0022] (ii) calcining the impregnated material of step (i) to obtain the calcined material;

[0023] (iii) mixing a sulfiding agent and the calcined material of step (ii) to obtain the activated carbon composite material.

[0024] The activated carbon composite material of the present invention can be prepared by liquid phase reduction or carbon thermal reduction, which is not only simple to operate, low in cost, and easy to promote and apply, but also the preparation method of the present invention can simultaneously sulfidize the loaded zero-valent iron and silver to obtain a sulfided bimetallic composite activated carbon material; wherein, during the liquid phase reduction process, the present invention simultaneously reduces iron and silver to the surface of the activated carbon, and then simultaneously sulfidizes them, thereby realizing the sulfidation of the zero-valent iron and silver surfaces; in the carbon thermal reduction method, the present invention can directly use biomass carbonized materials for preparation or directly use activated carbon for preparation. Compared with directly using activated carbon for preparation, using biomass carbonized materials as raw materials saves energy consumption, does not require secondary processing of the activated carbon, can obtain activated carbon in the carbon thermal reduction process, and the performance of the obtained product will not be affected.

[0025] Preferably, the activated carbon in step (1) and step (i) is coconut shell activated carbon.

[0026] Preferably, the particle size of the activated carbon in step (1) and step (i) is independently 20-325 mesh, for example, 20 mesh, 100 mesh, 200 mesh, 300 mesh or 325 mesh, the strength is independently 95% or more, for example, 95%, 96%, 97%, 98% or 99%, and the specific surface area is independently 900m 2 / g or more, for example, 900m 2 / g、1000m 2 / g、1100m 2 / g or 1200m 2 / g, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] The strength of the activated carbon of the present invention can reflect the powder loss rate of the activated carbon after grinding. When the strength is above 95%, the loss rate of the activated carbon after grinding is below 5%.

[0028] Preferably, the activated carbon in step (1) is washed and dried before being mixed with the impregnation solution.

[0029] Preferably, the cleaning solution comprises ultrapure water, and the cleaning is performed until the pH of the cleaning solution is 6.5-7.5, for example, 6.5, 7.0 or 7.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the drying temperature is 100-110°C, such as 100°C, 105°C or 110°C, and the drying time is 12-48h, such as 12h, 36h or 48h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the impregnation solutions in step (1) and step (i) are both obtained by mixing a ferrous source, a silver source and a solvent.

[0032] The impregnation solution of the present invention is obtained by stirring and mixing a ferrous source, a silver source and a solvent at room temperature for 2-12 hours, for example, 2 hours, 5 hours, 10 hours or 12 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the solvent includes ethanol, water and polyethylene glycol.

[0034] Preferably, the volume ratio of ethanol to water is (1-2):(3-9), for example, 1:3, 1.5:5 or 2:9, and the volume ratio of polyethylene glycol to water is (0.0022-0.0033):1, for example, 0.0022:1, 0.0027:1 or 0.0033:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the molecular weight of the polyethylene glycol is 200-4000 g / mol, for example, 200 g / mol, 1000 g / mol, 2000 g / mol, 3000 g / mol or 4000 g / mol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, in the mixed solution of step (1), the mass of the ferrous source is 6.0-10.0% of the mass of the activated carbon in step (1), for example, it can be 6.0%, 7.0%, 8.0%, 9.0% or 10.0%, and the mass of the silver source is 0.06-0.30% of the mass of the activated carbon in step (1), for example, it can be 0.06%, 0.1%, 0.2% or 0.30%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, in the mixed solution obtained by the impregnation in step (i), the mass of the ferrous source is 6.0-10.0% of the mass of the activated carbon and / or biomass carbonized material in step (1), for example, it can be 6.0%, 7.0%, 8.0%, 9.0% or 10.0%, and the mass of the silver source is 0.06-0.30% of the mass of the activated carbon and / or biomass carbonized material in step (1), for example, it can be 0.06%, 0.1%, 0.2% or 0.30%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] The mass relationship between the carbon raw material and the ferrous source of the present invention is within a preferred range, which can simultaneously ensure the various properties of the composite material. If the mass of iron is less than that of the carbon raw material, the performance of the activated carbon will not be sufficiently improved; if the mass of iron is too much compared to the carbon raw material, the pore structure and adsorption efficiency of the activated carbon itself will be significantly reduced, causing secondary pollution problems due to iron loss.

[0039] Preferably, the mixing time in step (1) and the immersion time in step (i) are independently 12-24 h, for example, 12 h, 18 h or 24 h, and the temperature is independently 20-35 ° C, for example, 20 ° C, 25 ° C, 30 ° C or 35 ° C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the reducing agent in step (2) comprises sodium borohydride.

[0041] The sodium borohydride described in the present invention is in solution state.

[0042] Preferably, the ratio of the volume of the reducing agent in step (2) to the volume of the mixed solution in step (1) is (0.9-1.1):1, for example, it can be 0.9:1, 1:1 or 1.1:1, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0043] Preferably, the mass of the reducing agent in step (2) is 0.8-5 g, for example, 0.8 g, 1 g, 2 g, 3 g, 4 g or 5 g, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] Preferably, the reducing agent in step (2) is added dropwise at a rate of 0.1-0.5 mL / min, for example, 0.1 mL / min, 0.3 mL / min or 0.5 mL / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0045] Preferably, after the reducing agent is added in step (2), the reaction is continued for 60-120 minutes before adding the sulfiding agent, for example, 60 minutes, 80 minutes, 100 minutes or 120 minutes, but the time is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] Preferably, the sulfiding agent in step (2) and the Fe 2+ The molar ratio is (0.2-0.8):1, for example, it can be 0.2:1, 0.4:1, 0.6:1 or 0.8:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] The molar ratio of the vulcanizing agent to the iron ions in the impregnation solution of the present invention will affect the vulcanization effect and the performance of the composite material. 2+ If the molar ratio of the sulfiding agent to the Fe in step (1) is too large, a passivation layer is easily formed on the iron surface, and too many core iron atoms are consumed, resulting in a decrease in the performance of the iron. 2+ If the molar ratio of is too small, the oxygen atoms on the iron surface cannot be completely replaced, the hydrophobicity of the surface is not effectively enhanced, and the selectivity of the pollutants is not enhanced.

[0048] Preferably, the vulcanizing agent in step (2) and the Ag in step (1) + The molar ratio is (7.0-154.0):1, for example, it can be 7.0:1, 10:1, 20.0:1, 30.0:1, 40.0:1, 50.0:1, 60.0:1, 70.0:1, 80.0:1, 90.0:1, 100.0:1, 110.0:1, 120.0:1, 130.0:1, 140.0:1 or 150.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] The vulcanizing agent of the present invention and the Ag in step (1) + If the molar ratio of silver to iron is too large, the silver surface will be too passivated, resulting in a decrease in antibacterial ability; at the same time, the microbattery reaction between silver and iron will be weakened, which is not conducive to the removal of pollutants in water; finally, secondary pollution may occur due to excessive sulfur content. + The molar ratio of is too small, which has little effect on reducing the risk of silver release.

[0050] Preferably, the sulfiding agent is added in step (2) by dropwise adding the sulfiding agent solution for 120-480 min, for example, 120 min, 360 min or 480 min. After the addition is completed, the reaction is continued for 30-120 min, for example, 30 min, 60 min or 120 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0051] Preferably, the sulfiding agent in step (2) comprises sulfide, and the sulfide comprises sodium sulfide.

[0052] Preferably, after the vulcanization in step (2), solid-liquid separation and freeze-drying are performed to obtain the activated carbon composite material.

[0053] Preferably, the freeze-drying time is 48-72 hours, for example, 48 hours, 56 hours or 72 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the biomass carbonized material in step (i) is coconut shell biomass carbonized material.

[0055] Preferably, the mesh size of the biomass carbonized material in step (i) is 20-325 meshes, for example, 20 meshes, 100 meshes, 200 meshes or 325 meshes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] Preferably, the biomass carbonized material in step (i) is washed and dried before impregnation.

[0057] Preferably, the cleaning time is 12-24 hours, for example, 12 hours, 18 hours or 24 hours, and the drying time is 24-72 hours, for example, 24 hours, 38 hours, 56 hours or 72 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, after the solid-liquid separation in step (i), the impregnated material is dried at 100-110°C, for example, 100°C, 105°C or 110°C, for 24-48h, for example, 24h, 36h or 48h to obtain the impregnated material.

[0059] Preferably, the calcination temperature in step (ii) is 500-600°C, such as 500°C, 550°C or 600°C, the time is 0.5-2h, such as 0.5h, 1h or 2h, and the atmosphere is nitrogen atmosphere.

[0060] Preferably, in step (ii), the calcined material is first activated with water vapor, then carbonized in a nitrogen atmosphere, and then mixed with a sulfiding agent.

[0061] Preferably, the time for continuing carbonization in the nitrogen atmosphere is 1-3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0062] In the steam activation step of the present invention, carbon atoms on the surface of the carbonized material react with the steam to generate carbon oxides and hydrogen, and the consumed carbon atoms generate holes.

[0063] Preferably, during the water vapor activation process, the water vapor introduction rate is 0.1-0.5 mL / min, for example, it can be 0.1 mL / min, 0.2 mL / min, 0.3 mL / min, 0.4 mL / min or 0.5 mL / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0064] If the water vapor introduction rate of the present invention is too high, it may cause excessive burning of carbon atoms, thereby reducing the yield of the carbon material; if the water vapor introduction rate is too low, it may cause insufficient reaction of carbon atoms, ultimately resulting in insufficient pore formation.

[0065] Preferably, the water vapor activation temperature is 850-950°C, for example, 850°C, 900°C or 950°C, and the time is 30-60min, for example, 30min, 45min or 60min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] Preferably, the sulfiding agent in step (iii) and the Fe 2+ The molar ratio is (0.2-0.8):1, for example, it can be 0.2:1, 0.4:1, 0.6:1 or 0.8:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] Preferably, the sulfurizing agent in step (iii) and the Ag in step (i) + The molar ratio is (7.0-154.0):1, for example, it can be 7.0:1, 10:1, 20.0:1, 30.0:1, 40.0:1, 50.0:1, 60.0:1, 70.0:1, 80.0:1, 90.0:1, 100.0:1, 110.0:1, 120.0:1, 130.0:1, 140.0:1 or 150.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the mixing method in step (iii) is: adding the solution of the sulfiding agent dropwise to the calcined material, the addition time is 120-480 minutes, for example, it can be 120 minutes, 360 minutes or 480 minutes, and the reaction is continued for 30-120 minutes after the addition is completed, for example, it can be 30 minutes, 60 minutes or 120 minutes, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0069] Preferably, the sulfiding agent in step (iii) comprises sulfide, and the sulfide comprises sodium sulfide.

[0070] Preferably, after the mixing in step (iii), solid-liquid separation and freeze-drying are further performed to obtain the activated carbon composite material.

[0071] Preferably, the freeze-drying time is 48-72 hours, for example, 48 hours, 56 hours or 72 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0073] The preparation method includes a liquid phase reduction method or a carbon thermal reduction method;

[0074] The liquid phase reduction method comprises the following steps:

[0075] (1) mixing the activated carbon and the impregnation solution at 20-35° C. for 12-24 hours to obtain a mixed solution;

[0076] The impregnation solution includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to the water is (1-2):(3-9), the volume ratio of the polyethylene glycol to the water is (0.0022-0.0033):1, and the molecular weight of the polyethylene glycol is 200-4000 g / mol;

[0077] In the mixed solution, the mass of the ferrous source is 6.0-10.0% of the mass of the activated carbon, and the mass of the silver source is 0.06-0.30% of the mass of the activated carbon;

[0078] (2) adding a reducing agent dropwise to the mixed solution of step (1) at a rate of 0.1-0.5 mL / min for reduction, and after the addition of the reducing agent, continuing the reaction for 60-120 min, and then adding a solution of a sulfiding agent dropwise for 120-480 min, and after the addition is completed, continuing the reaction for 30-120 min, and after the sulfidation is completed, performing solid-liquid separation and freeze-drying to obtain the activated carbon composite material;

[0079] The ratio of the volume of the reducing agent to the volume of the mixed solution in step (1) is (0.9-1.1):1; the ratio of the volume of the sulfiding agent to the volume of the Fe 2+ The molar ratio is (0.2-0.8):1;

[0080] The carbothermal reduction method comprises the following steps:

[0081] (i) impregnating the biomass carbonized material at 20-35° C. for 12-24 hours, then performing solid-liquid separation, and then drying at 100-110° C. for 24-48 hours to obtain an impregnated material;

[0082] The impregnation solution used in the impregnation includes Fe 2+ and Ag +, obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to the water is (1-2):(3-9), the volume ratio of the polyethylene glycol to the water is (0.0022-0.0033):1, and the molecular weight of the polyethylene glycol is 200-4000 g / mol;

[0083] In the mixed solution obtained by the impregnation, the mass of the ferrous source is 6.0-10.0% of the mass of the biomass carbonized material, and the mass of the silver source is 0.06-0.30% of the mass of the biomass carbonized material;

[0084] (ii) calcining the impregnated material in step (i) at a temperature of 500-600° C. in a nitrogen atmosphere to obtain the calcined material, and then activating the impregnated material with water vapor at a temperature of 850-950° C. for 30-60 min at a water vapor introduction rate of 0.1-0.5 mL / min, and then carbonizing the impregnated material in a nitrogen atmosphere for 1-3 h to obtain an activated material;

[0085] (iii) adding a solution of a sulfiding agent dropwise to the activated material in step (ii) for 120-480 min, continuing the reaction for 30-120 min after the addition is completed, and then performing solid-liquid separation and freeze-drying to obtain the activated carbon composite material;

[0086] The sulfiding agent and the Fe 2+ The molar ratio is (0.2-0.8):1.

[0087] In a third aspect, the present invention provides an application of the activated carbon composite material as described in the first aspect, wherein the application includes use for treating disinfection by-products and heavy metal ions in water while inhibiting the reproduction of surface microorganisms.

[0088] For example, treating substances such as trihalomethanes, N-nitrosodimethylamine (NDMA), lead and cadmium in water.

[0089] Compared with the prior art, the present invention has the following beneficial effects:

[0090] The activated carbon composite material of the present invention can not only enhance the hydrophobicity, electron transfer ability and pollutant molecule selectivity of the material surface, but also has antibacterial properties and can weaken the release of silver ions. It combines the advantages of efficient electron transfer, strong surface hydrophobicity, high pollutant selectivity and inhibition of microbial reproduction on the carbon surface. It can safely and effectively adsorb and degrade or convert low-concentration pollutants in drinking water, and significantly improve the water purification capacity of activated carbon from many aspects. The activated carbon composite material of the present invention is synthesized by sulfurization after carbon thermal reduction or liquid phase reduction, and the method is simple to operate and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0091] Figure 1 This is a SEM image of the activated carbon composite material described in Example 1 of the present invention at a scale of 5 μm;

[0092] Figure 2 This is a SEM image of the activated carbon composite material described in Example 1 of the present invention at a scale of 10 nm. DETAILED DESCRIPTION

[0093] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0094] Example 1

[0095] This embodiment provides an activated carbon composite material. The SEM image of the activated carbon composite material at a scale of 5 μm is as follows: Figure 1 As shown, the SEM image at 10nm scale is Figure 2 As shown, the activated carbon composite material includes activated carbon and an active component loaded on the activated carbon; the active component includes zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the particle size of the zero-valent iron is 20-30nm, the thickness of the iron sulfide on the surface of the zero-valent iron is 1-3nm, the particle size of the silver is 20-30nm, and the thickness of the silver sulfide on the surface of the silver is 1-3nm;

[0096] The preparation method of the activated carbon composite material comprises the following steps:

[0097] (i) soaking the biomass carbonized material at 25° C. for 18 hours, filtering it, and then drying it at 105° C. for 36 hours to obtain an impregnated material;

[0098] The biomass carbonized material is coconut shell carbonized material with a mesh size of 150 meshes. The biomass carbonized material is washed for 16 hours and then dried for 48 hours before impregnation;

[0099] The impregnation solution used in the impregnation includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the ferrous salt is FeSO4·7H2O, and the silver source is AgNO3; the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to water is 1.5:7, the volume ratio of the polyethylene glycol to water is 0.003:1, and the molecular weight of the polyethylene glycol is 200 g / mol;

[0100] In the mixed solution obtained by the impregnation, the mass of the ferrous source is 8% of the mass of the biomass carbonized material, and the mass of the silver source is 0.18% of the mass of the biomass carbonized material;

[0101] (ii) calcining the impregnated material in step (i) at 550° C. for 80 min in a nitrogen atmosphere to obtain the calcined material, and then activating the impregnated material with water vapor at 900° C. for 30 min at a water vapor introduction rate of 0.5 mL / min, and carbonizing the impregnated material in a nitrogen atmosphere for 1.5 h to obtain an activated material;

[0102] (iii) adding a solution of a sulfiding agent dropwise to the activated material in step (ii) for 300 min, continuing the reaction for 60 min after the addition is completed, and then filtering and freeze-drying for 52 h to obtain the activated carbon composite material;

[0103] The sulfiding agent is sodium sulfide, and the sulfiding agent and the Fe 2+ The molar ratio of the sulfurizing agent to the Ag in step (1) is 0.5:1. + The molar ratio is 43:1.

[0104] Example 2

[0105] The present embodiment provides an activated carbon composite material, the activated carbon composite material comprising activated carbon and an active component supported on the activated carbon; the active component comprises zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the particle size of the zero-valent iron is 30-50nm, the thickness of the iron sulfide on the surface of the zero-valent iron is 1-3nm, the particle size of the silver is 30-50nm, and the thickness of the silver sulfide on the surface of the silver is 1-3nm;

[0106] The preparation method of the activated carbon composite material comprises the following steps:

[0107] (i) impregnating the biomass carbonized material at 35° C. for 12 h, filtering it, and then drying it at 110° C. for 24 h to obtain an impregnated material;

[0108] The biomass carbonized material is coconut shell carbonized material with a mesh size of 20. The biomass carbonized material is washed for 24 hours and then dried for 72 hours before impregnation.

[0109] The impregnation solution used in the impregnation includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the ferrous salt is FeSO4·7H2O, and the silver source is AgNO3; the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to water is 1:3, the volume ratio of the polyethylene glycol to water is 0.0022:1, and the molecular weight of the polyethylene glycol is 4000g / mol;

[0110] In the mixed solution obtained by the impregnation, the mass of the ferrous source is 10.0% of the mass of the biomass carbonized material, and the mass of the silver source is 0.30% of the mass of the biomass carbonized material;

[0111] (ii) calcining the impregnated material in step (i) at 500° C. for 120 min in a nitrogen atmosphere to obtain the calcined material, and then activating the impregnated material with water vapor at 850° C. for 45 min at a water vapor introduction rate of 0.2 mL / min, and carbonizing the impregnated material in a nitrogen atmosphere for 1 h to obtain an activated material;

[0112] (iii) adding a solution of a sulfiding agent dropwise to the activated material in step (ii) for 480 min, continuing the reaction for 30 min after the addition is completed, and then filtering and freeze-drying for 48 h to obtain the activated carbon composite material;

[0113] The sulfiding agent is sodium sulfide, and the sulfiding agent and the Fe 2+ The molar ratio of the sulfurizing agent to the Ag in step (1) is 0.8:1. + The molar ratio is 51:1.

[0114] Example 3

[0115] The present embodiment provides an activated carbon composite material, the activated carbon composite material comprising activated carbon and an active component supported on the activated carbon; the active component comprises zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the particle size of the zero-valent iron is 40-50nm, the thickness of the iron sulfide on the surface of the zero-valent iron is 1-3nm, the particle size of the silver is 20-30nm, and the thickness of the silver sulfide on the surface of the silver is 1-3nm;

[0116] The preparation method of the activated carbon composite material comprises the following steps:

[0117] (i) impregnating the biomass carbonized material at 20° C. for 24 hours, filtering it, and then drying it at 100° C. for 48 hours to obtain an impregnated material;

[0118] The biomass carbonized material is coconut shell carbonized material with a mesh size of 80 meshes. The biomass carbonized material is washed for 12 hours and then dried for 24 hours before impregnation;

[0119] The impregnation solution used in the impregnation includes Fe 2+ and Ag +, obtained by mixing a ferrous source, a silver source and a solvent, wherein the ferrous salt is FeSO4·7H2O, and the silver source is AgNO3; the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to water is 2:9, the volume ratio of the polyethylene glycol to water is 0.0033:1, and the molecular weight of the polyethylene glycol is 400g / mol;

[0120] In the mixed solution obtained by the impregnation, the mass of the ferrous source is 6.0% of the mass of the biomass carbonized material, and the mass of the silver source is 0.06% of the mass of the biomass carbonized material;

[0121] (ii) calcining the impregnated material in step (i) at 600° C. for 30 min in a nitrogen atmosphere to obtain the calcined material, and then activating the impregnated material with water vapor at 950° C. for 30 min at a water vapor introduction rate of 0.1 mL / min, and carbonizing the impregnated material in a nitrogen atmosphere for 2.5 h to obtain an activated material;

[0122] (iii) adding a solution of a sulfiding agent dropwise to the activated material in step (ii) for 120 min, continuing the reaction for 120 min after the addition is completed, and then filtering and freeze-drying for 72 h to obtain the activated carbon composite material;

[0123] The sulfiding agent is sodium sulfide, and the sulfiding agent and the Fe 2+ The molar ratio of the sulfurizing agent to the Ag in step (1) is 0.2:1. + The molar ratio is 39:1.

[0124] Example 4

[0125] The present embodiment provides an activated carbon composite material, the activated carbon composite material comprising activated carbon and an active component supported on the activated carbon; the active component comprises zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the particle size of the zero-valent iron is 20-30 nm, the thickness of the iron sulfide on the surface of the zero-valent iron is 1-3 nm, the particle size of the silver is 20-30 nm, and the thickness of the silver sulfide on the surface of the silver is 1-3 nm;

[0126] The preparation method of the activated carbon composite material comprises the following steps:

[0127] (1) mixing the activated carbon and the impregnation solution at 25° C. for 18 hours to obtain a mixed solution;

[0128] The activated carbon is coconut shell activated carbon, which has a mesh size of 150 meshes, a strength of 98%, and a specific surface area of ​​1000 m 2 / g; the activated carbon is washed and dried at 105°C for 36h before being mixed with the impregnation solution, the washing solution comprising ultrapure water, and the washing is performed until the pH of the washing solution is 7;

[0129] The impregnation solution includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol; wherein the ferrous salt is FeSO4·7H2O, and the silver source is AgNO3; the volume ratio of the ethanol to water is 1.5:7, the volume ratio of the polyethylene glycol to water is 0.003:1, and the molecular weight of the polyethylene glycol is 200 g / mol;

[0130] In the mixed solution, the mass of the ferrous source is 8% of the mass of the activated carbon, and the mass of the silver source is 0.18% of the mass of the activated carbon;

[0131] (2) adding a reducing agent dropwise to the mixed solution of step (1) at a rate of 0.3 mL / min for reduction, and after the addition of the reducing agent, continuing the reaction for 80 min, and then adding a solution of a sulfiding agent dropwise for 360 min, and after the addition is completed, continuing the reaction for 80 min, filtering and freeze-drying for 60 h after the sulfidation is completed, to obtain the activated carbon composite material;

[0132] The reducing agent is a sodium borohydride solution with a concentration of 4.12%, the mass of the reducing agent is 4.3 g, and the ratio of the volume of the reducing agent to the volume of the mixed solution in step (1) is 1:1; the sulfiding agent is sodium sulfide, and the sulfiding agent and the Fe 2+ The molar ratio of the sulfurizing agent to the Ag in step (1) is 0.5:1. + The molar ratio is 43:1.

[0133] Example 5

[0134] The present embodiment provides an activated carbon composite material, the activated carbon composite material comprising activated carbon and an active component supported on the activated carbon; the active component comprises zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the particle size of the zero-valent iron is 40-50nm, the thickness of the iron sulfide on the surface of the zero-valent iron is 1-3nm, the particle size of the silver is 30-40nm, and the thickness of the silver sulfide on the surface of the silver is 1-3nm;

[0135] The preparation method of the activated carbon composite material comprises the following steps:

[0136] (1) mixing the activated carbon and the impregnation solution at 35° C. for 12 h to obtain a mixed solution;

[0137] The activated carbon is coconut shell activated carbon, which has a mesh size of 20 meshes, a strength of 95%, and a specific surface area of ​​900 m 2 / g; the activated carbon is washed and dried at 110°C for 12h before being mixed with the impregnation solution, the washing solution comprising ultrapure water, and the washing is performed until the pH of the washing solution is 6.5;

[0138] The impregnation solution includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol, wherein the ferrous salt is FeSO4·7H2O, and the silver source is AgNO3; the volume ratio of the ethanol to water is 1:3, the volume ratio of the polyethylene glycol to water is 0.0022:1, and the molecular weight of the polyethylene glycol is 4000g / mol;

[0139] In the mixed solution, the mass of the ferrous source is 10.0% of the mass of the activated carbon, and the mass of the silver source is 0.30% of the mass of the activated carbon;

[0140] (2) adding a reducing agent dropwise to the mixed solution of step (1) at a rate of 0.1 mL / min for reduction, and after the addition of the reducing agent, continuing the reaction for 60 min, and then adding a solution of a sulfiding agent dropwise for 480 min, and after the addition is completed, continuing the reaction for 30 min, filtering and freeze-drying for 72 h after the sulfidation is completed, to obtain the activated carbon composite material;

[0141] The reducing agent is a sodium borohydride solution with a concentration of 2.64%, the mass of the reducing agent is 2.71 g, and the ratio of the volume of the reducing agent to the volume of the mixed solution in step (1) is 1.1:1; the sulfiding agent is sodium sulfide, and the sulfiding agent and the Fe 2+ The molar ratio of the sulfurizing agent to the Ag in step (1) is 0.8:1. + The molar ratio is 51:1.

[0142] Example 6

[0143] The present embodiment provides an activated carbon composite material, the activated carbon composite material comprising activated carbon and an active component supported on the activated carbon; the active component comprises zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; the particle size of the zero-valent iron is 40-50nm, the thickness of the iron sulfide on the surface of the zero-valent iron is 1-3nm, the particle size of the silver is 40-50nm, and the thickness of the silver sulfide on the surface of the silver is 1-3nm;

[0144] The preparation method of the activated carbon composite material comprises the following steps:

[0145] (1) mixing the activated carbon and the impregnation solution at 20° C. for 24 hours to obtain a mixed solution;

[0146] The activated carbon is coconut shell activated carbon, which has a mesh size of 80 meshes, a strength of 96%, and a specific surface area of ​​900 m 2 / g; the activated carbon is washed and dried at 100°C for 48h before being mixed with the impregnation solution, the washing solution comprising ultrapure water, and the washing is performed until the pH of the washing solution is 7.5;

[0147] The impregnation solution includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol, wherein the ferrous salt is FeSO4·7H2O, and the silver source is AgNO3; the volume ratio of the ethanol to water is 2:9, the volume ratio of the polyethylene glycol to water is 0.0033:1, and the molecular weight of the polyethylene glycol is 400g / mol;

[0148] In the mixed solution, the mass of the ferrous source is 6.0% of the mass of the activated carbon, and the mass of the silver source is 0.06% of the mass of the activated carbon;

[0149] (2) adding a reducing agent dropwise to the mixed solution of step (1) at a rate of 0.5 mL / min for reduction, and after the addition of the reducing agent, continuing the reaction for 120 min, and then adding a solution of a sulfiding agent dropwise for 120 min, and after the addition is completed, continuing the reaction for 120 min, filtering and freeze-drying for 48 h after the sulfidation is completed, to obtain the activated carbon composite material;

[0150] The reducing agent is a sodium borohydride solution with a concentration of 0.80%, the mass of the reducing agent is 0.81 g, and the ratio of the volume of the reducing agent to the volume of the mixed solution in step (1) is 0.9:1; the sulfiding agent is sodium sulfide, and the sulfiding agent and the Fe 2+ The molar ratio of the sulfurizing agent to the Ag in step (1) is 0.2:1. + The molar ratio is 39:1.

[0151] Example 7

[0152] This embodiment provides an activated carbon composite material, which is the same as that of Example 1 except that in the preparation method, the mass of the biomass carbonized material in step (i) is replaced by activated carbon, so that the obtained activated carbon composite material is changed accordingly. The mesh number of the activated carbon is 150 meshes, the strength is 98%, and the specific surface area is 1000m 2 / g.

[0153] Example 8

[0154] This embodiment provides an activated carbon composite material, which is the same as that of Example 1 except that in the preparation method, the mass of the ferrous source in step (i) is 3% of the mass of the biomass carbonized material, so that the obtained activated carbon composite material changes accordingly.

[0155] Example 9

[0156] This embodiment provides an activated carbon composite material, which is the same as that of Example 1 except that in the preparation method, the mass of the ferrous source in step (i) is 15% of the mass of the biomass carbonized material, so that the obtained activated carbon composite material changes accordingly.

[0157] Example 10

[0158] This embodiment provides an activated carbon composite material, which is the same as that of Example 1 except that in the preparation method, the introduction rate of water vapor in step (ii) is 0.05 mL / min, which causes the obtained activated carbon composite material to change accordingly.

[0159] Embodiment 11

[0160] This embodiment provides an activated carbon composite material, which is the same as that of Example 1 except that in the preparation method, the introduction rate of water vapor in step (ii) is 0.8 mL / min, which causes the obtained activated carbon composite material to change accordingly.

[0161] Example 12

[0162] This embodiment provides an activated carbon composite material, wherein in addition to the preparation method, the sulfiding agent in step (iii) and the Fe 2+ The molar ratio of the sulfurizing agent in step (iii) and the Ag in step (i) is 0.1:1. + The molar ratio of is 8.6:1, and the activated carbon composite material obtained is changed accordingly, and the rest is the same as Example 1.

[0163] Embodiment 13

[0164] This embodiment provides an activated carbon composite material, wherein in addition to the preparation method, the sulfiding agent in step (iii) and the Fe 2+ The molar ratio of the sulfurizing agent in step (iii) and the Ag in step (i) is 1:1. + The molar ratio of is 85.6:1, and the activated carbon composite material obtained is changed accordingly, and the rest is the same as Example 1.

[0165] Embodiment 14

[0166] This embodiment provides an activated carbon composite material, wherein in addition to the preparation method, the sulfiding agent in step (iii) and the Fe 2+ The molar ratio of the sulfurizing agent in step (iii) to the Ag in step (i) is 0.04:1. + The molar ratio of is 3:1, and the obtained activated carbon composite material is changed accordingly, and the rest is the same as Example 1.

[0167] Embodiment 15

[0168] This embodiment provides an activated carbon composite material, wherein in addition to the preparation method, the sulfiding agent in step (iii) and the Fe 2+ The molar ratio of the sulfurizing agent in step (iii) and the Ag in step (i) is 2:1. + The molar ratio of is 180:1, and the activated carbon composite material obtained is changed accordingly, and the rest is the same as Example 1.

[0169] Comparative Example 1

[0170] This comparative example provides an activated carbon composite material, which is the same as Example 1 except that the surface of the zero-valent iron is not coated with iron sulfide and the surface of the silver is not coated with silver sulfide.

[0171] The preparation method of the activated carbon composite material is the same as that of Example 1 except that step (iii) is not performed.

[0172] Comparative Example 2

[0173] This comparative example provides an activated carbon composite material, which is the same as Example 4 except that the surface of the zero-valent iron is not coated with iron sulfide and the surface of the silver is not coated with silver sulfide;

[0174] The preparation method of the activated carbon composite material is the same as that of Example 4, except that no vulcanizing agent is added for vulcanization after reduction in step (2), but filtering and freeze-drying are performed directly after reduction.

[0175] The activated carbon composite materials obtained in the above examples and comparative examples are used to selectively treat pollutants in water, such as heavy metal ions, disinfection byproducts, etc. Among them, the heavy metal ions are lead ions, and the initial concentration is determined to be 1 mg / L, the initial pH value is 6.8, the amount of composite material added is 2 g / L, and the adsorption time is 1 h. For disinfection byproducts such as N-nitrosodimethylamine (NDMA), the initial concentration is determined to be 10 μg / L, the initial pH value is 7.0, the amount of composite material added is 0.5 g / L, and the adsorption time is 12 h.

[0176] The test results are shown in the following table:

[0177] Table 1

[0178]

[0179]

[0180] From the above table we can see that:

[0181] The activated carbon composite material provided by the present invention improves the selectivity of pollutants, reduces the risk of metal ion loss, and inhibits the growth of microbial film on the surface of activated carbon; and from the comparison of Example 1, Example 4, Comparative Example 1 and Comparative Example 2, it can be seen that the present invention simultaneously sulfides zero-valent iron and silver, which can avoid the problem that iron and silver are easy to react with water molecules, causing the selectivity to decrease and the reaction ratio to decrease; from Example 1 and Example 7, it can be seen that when the present invention adopts carbon thermal reduction for preparation, the raw material adopts carbonized material and still can obtain an activated carbon composite material with excellent performance; from Examples 8-15, it can be seen that the amount of ferrous salt and carbon raw material used in the present invention, the amount of water vapor introduced, the molar ratio of the sulfiding agent to iron, and the molar ratio of the sulfiding agent to silver will all affect the performance of the activated carbon composite material.

[0182] In summary, the present invention provides an activated carbon composite material and a preparation method and application thereof. The activated carbon composite material is simultaneously loaded with sulfided nano-zero-valent iron and sulfided nano-silver, which improves the selectivity of pollutants, reduces the risk of metal ion loss, inhibits the growth of microbial film on the surface of activated carbon, and degrades some organic matter in water in situ.

[0183] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An activated carbon composite material, characterized in that: The activated carbon composite material comprises activated carbon and an active component loaded on the activated carbon; The active components include zero-valent iron and silver, the surface of the zero-valent iron is coated with iron sulfide, and the surface of the silver is coated with silver sulfide; The preparation method of the activated carbon composite material includes a liquid phase reduction method or a carbon thermal reduction method; The liquid phase reduction method comprises the following steps: (1) mixing the activated carbon with the impregnation solution to obtain a mixed solution; The impregnation solution includes Fe 2+ and Ag + ; (2) adding a reducing agent to the mixed solution of step (1) for reduction, and then adding a vulcanizing agent for vulcanization to obtain the activated carbon composite material; The carbothermal reduction method comprises the following steps: (i) impregnating activated carbon and / or biomass carbonized material, and then performing solid-liquid separation to obtain an impregnated material; The impregnation solution used in the impregnation includes Fe 2+ and Ag + ; (ii) calcining the impregnated material of step (i) to obtain a calcined material; (iii) mixing a sulfiding agent and the calcined material of step (ii) to obtain the activated carbon composite material.

2. The activated carbon composite material according to claim 1, characterized in that The particle size of the zero-valent iron is in the range of 20-50 nm, and the thickness of the iron sulfide on the surface of the zero-valent iron is in the range of 1-3 nm.

3. The activated carbon composite material according to claim 1 or 2, characterized in that: The particle size of the silver is in the range of 10-30 nm, and the thickness of the silver sulfide on the surface of the silver is in the range of 1-3 nm.

4. A method for preparing an activated carbon composite material according to any one of claims 1 to 3, characterized in that: The preparation method includes a liquid phase reduction method or a carbon thermal reduction method; The liquid phase reduction method comprises the following steps: (1) mixing the activated carbon with the impregnation solution to obtain a mixed solution; The impregnation solution includes Fe 2+ and Ag + ; (2) adding a reducing agent to the mixed solution of step (1) for reduction, and then adding a vulcanizing agent for vulcanization to obtain the activated carbon composite material; The carbothermal reduction method comprises the following steps: (i) impregnating activated carbon and / or biomass carbonized material, and then performing solid-liquid separation to obtain an impregnated material; The impregnation solution used in the impregnation includes Fe 2+ and Ag + ; (ii) calcining the impregnated material of step (i) to obtain a calcined material; (iii) mixing a sulfiding agent and the calcined material of step (ii) to obtain the activated carbon composite material.

5. The preparation method according to claim 4, characterized in that: The activated carbon in step (1) and step (i) is coconut shell activated carbon.

6. The preparation method according to claim 4, characterized in that: The particle size of the activated carbon in step (1) and step (i) is independently 20-325 mesh, the strength is independently 95% or more, and the specific surface area is independently 900m 2 / g or above.

7. The preparation method according to claim 4, characterized in that: The activated carbon in step (1) is washed and dried before being mixed with the impregnation solution.

8. The preparation method according to claim 4, characterized in that: The impregnation solutions in step (1) and step (i) are both obtained by mixing a ferrous source, a silver source and a solvent.

9. The preparation method according to claim 8, characterized in that: The solvents include ethanol, water and polyethylene glycol.

10. The preparation method according to claim 9, characterized in that: The volume ratio of the ethanol to water is (1-2):(3-9), and the volume ratio of the polyethylene glycol to water is (0.0022-0.0033):

1.

11. The preparation method according to claim 9, characterized in that: The molecular weight of the polyethylene glycol is 200-4000 g / mol.

12. The preparation method according to claim 4, characterized in that: In the mixed solution of step (1), the mass of the ferrous source is 6.0-10.0% of the mass of the activated carbon, and the mass of the silver source is 0.06-0.30% of the mass of the activated carbon.

13. The preparation method according to claim 4, characterized in that: In the mixed solution obtained by the impregnation in step (i), the mass of the ferrous source is 6.0-10.0% of the mass of the activated carbon and / or biomass carbonized material in step (1), and the mass of the silver source is 0.06-0.30% of the mass of the activated carbon and / or biomass carbonized material in step (1).

14. The preparation method according to claim 4, characterized in that: The time for the mixing in step (1) and the immersion in step (i) is independently 12-24 hours, and the temperature is independently 20-35°C.

15. The preparation method according to claim 4, characterized in that: The reducing agent in step (2) includes sodium borohydride.

16. The preparation method according to claim 4, characterized in that: The ratio of the volume of the reducing agent in step (2) to the volume of the mixed solution in step (1) is (0.9-1.1):

1.

17. The preparation method according to claim 4, characterized in that: The reducing agent in step (2) is added dropwise at a rate of 0.1-0.5 mL / min.

18. The preparation method according to claim 4, characterized in that: After the reducing agent is added in step (2), the reaction is continued for 60-120 minutes, and then the sulfiding agent is added.

19. The preparation method according to claim 4, characterized in that: The sulfiding agent in step (2) and the Fe in step (1) 2+ The molar ratio is (0.2-0.8):

1.

20. The preparation method according to claim 4, characterized in that: The sulfurizing agent in step (2) and the Ag in step (1) + The molar ratio is (7.0-154.0):

1.

21. The preparation method according to claim 4, characterized in that: The method of adding the sulfiding agent in step (2) is as follows: adding the sulfiding agent solution dropwise for 120-480 minutes, and continuing the reaction for 30-120 minutes after the addition is completed.

22. The preparation method according to claim 4, characterized in that: The sulfiding agent in step (2) includes sulfide, and the sulfide includes sodium sulfide.

23. The preparation method according to claim 4, characterized in that: After the vulcanization in step (2), solid-liquid separation and freeze-drying are performed to obtain the activated carbon composite material.

24. The preparation method according to claim 4, characterized in that: The biomass carbonized material in step (i) is coconut shell biomass carbonized material.

25. The preparation method according to claim 4, characterized in that: The mesh size of the biomass carbonized material in step (i) is 20-325 meshes.

26. The preparation method according to claim 4, characterized in that: In step (i), the biomass carbonized material is first cleaned and dried before impregnation.

27. The preparation method according to claim 4, characterized in that: After the solid-liquid separation in step (i), the impregnated material is dried at 100-110° C. for 24-48 hours to obtain the impregnated material.

28. The preparation method according to claim 4, characterized in that: The calcination temperature in step (ii) is 500-600° C., the calcination time is 30-120 min, and the atmosphere is nitrogen.

29. The preparation method according to claim 4, characterized in that: In step (ii), the calcined material is first activated by water vapor, then carbonized in a nitrogen atmosphere, and then mixed with a sulfiding agent.

30. The preparation method according to claim 29, characterized in that: During the water vapor activation process, the water vapor introduction rate is 0.1-0.5 mL / min.

31. The preparation method according to claim 29, characterized in that: The temperature of the water vapor activation is 850-950° C. and the time is 30-60 minutes.

32. The preparation method according to claim 4, characterized in that: The sulfiding agent in step (iii) and the Fe in step (i) 2+ The molar ratio is (0.2-0.8):

1.

33. The preparation method according to claim 4, characterized in that: The sulfurizing agent in step (iii) and the Ag in step (i) + The molar ratio is (7.0-154.0):

1.

34. The preparation method according to claim 4, characterized in that: The mixing method of step (iii) is: adding the solution of the sulfiding agent dropwise to the calcined material, the adding time is 120-480 minutes, and the reaction is continued for 30-120 minutes after the addition is completed.

35. The preparation method according to claim 4, characterized in that: The sulfiding agent in step (iii) comprises sulfide, and the sulfide comprises sodium sulfide.

36. The preparation method according to claim 4, characterized in that: After the mixing in step (iii), solid-liquid separation and freeze-drying are performed to obtain the activated carbon composite material.

37. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: The preparation method includes a liquid phase reduction method or a carbon thermal reduction method; The liquid phase reduction method comprises the following steps: (1) mixing the activated carbon and the impregnation solution at 20-35° C. for 12-24 hours to obtain a mixed solution; The impregnation solution includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to the water is (1-2):(3-9), the volume ratio of the polyethylene glycol to the water is (0.0022-0.0033):1, and the molecular weight of the polyethylene glycol is 200-4000 g / mol; In the mixed solution, the mass of the ferrous source is 6.0-10.0% of the mass of the activated carbon, and the mass of the silver source is 0.06-0.30% of the mass of the activated carbon; (2) adding a reducing agent dropwise to the mixed solution of step (1) at a rate of 0.1-0.5 mL / min for reduction, and after the addition of the reducing agent, continuing the reaction for 60-120 min, and then adding a solution of a sulfiding agent dropwise for 120-480 min, and after the addition is completed, continuing the reaction for 30-120 min, and after the sulfidation is completed, performing solid-liquid separation and freeze-drying to obtain the activated carbon composite material; The ratio of the volume of the reducing agent to the volume of the mixed solution in step (1) is (0.9-1.1):1; the ratio of the volume of the sulfiding agent to the volume of the Fe 2+ The molar ratio is (0.2-0.8):1; The carbothermal reduction method comprises the following steps: (i) impregnating the biomass carbonized material at 20-35° C. for 12-24 hours, then performing solid-liquid separation, and then drying at 100-110° C. for 24-48 hours to obtain an impregnated material; The impregnation solution used in the impregnation includes Fe 2+ and Ag + , obtained by mixing a ferrous source, a silver source and a solvent, wherein the solvent includes ethanol, water and polyethylene glycol, wherein the volume ratio of the ethanol to the water is (1-2):(3-9), the volume ratio of the polyethylene glycol to the water is (0.0022-0.0033):1, and the molecular weight of the polyethylene glycol is 200-4000 g / mol; In the mixed solution obtained by the impregnation, the mass of the ferrous source is 6.0-10.0% of the mass of the biomass carbonized material, and the mass of the silver source is 0.06-0.30% of the mass of the biomass carbonized material; (ii) calcining the impregnated material in step (i) at a temperature of 500-600° C. in a nitrogen atmosphere to obtain the calcined material, and then activating the impregnated material with water vapor at a temperature of 850-950° C. for 30-60 min at a water vapor introduction rate of 0.1-0.5 mL / min, and then carbonizing the impregnated material in a nitrogen atmosphere for 1-3 h to obtain an activated material; (iii) adding a solution of a sulfiding agent dropwise to the activated material in step (ii) for 120-480 min, continuing the reaction for 30-120 min after the addition is completed, and then performing solid-liquid separation and freeze-drying to obtain the activated carbon composite material; The sulfiding agent and the Fe 2+ The molar ratio is (0.2-0.8):

1.

38. A use of the activated carbon composite material according to any one of claims 1 to 3, characterized in that: The applications include treating disinfection byproducts and heavy metal ions in water while inhibiting the growth of surface microorganisms.

Citation Information

Patent Citations

  • Method for preparing activated carbon loaded vulcanized nano zero-valent iron composite material by one-step method

    CN114950357A